Program evaluation and review technique – Data envelopment analysis in benchmarking sustainable supply chain management of the potato chips industry - Billy Akhbar Nugraha; Arif Hidayat; Wike Agustin Prima Dania; Katsumori Hatanaka; Saville Ramadhona (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
Supply chain benchmarking of agroindustry can be done by emphasizing the perspective of sustainability. This paper aimed to analyze the efficiency of Sustainable Supply Chain Management (SSCM) in Micro, Small, and Medium Enterprises (MSMEs) and provided a prospective benchmark with the potato chips industry as a study case. Program Evaluation and Review Technique (PERT) estimated future input and output values to obtain prospective benchmarks and be added to the DEA formula later. Analytical Hierarchy Process (AHP) and Data Envelopment Analysis (DEA) methods were used to measure SSCM performance. The results showed that 17 of 20 Decision-Making Units (DMUs) were efficient (score 1). The other 3 DMUs were classified and got an efficiency score of 0.965, 0.955, and 0.995. In future estimates calculation, the efficiency score of one of the inefficient DMUs has changed to 1, while the other two got the scores of 0.996 and 0.980. The limitation of this research mainly comes from the scope of assessment, which is limited to the supply chain’s downstream sector and assesses only a limited number of MSMEs in a particular region. SSCM efficiency measurement variables were adjusted to be assessed and applied to MSMEs. PERT was also beneficial to gain future estimates of the assessment scope.